Tensile strength of welded joints in low carbon steel using metal inert gas (MIG) welding - Hendri Nurdin; Purwantono Purwantono; Khairul Umurani (invotek, 2021)
The development of technology that has penetrated the industrial sector is very rapid. Many industrial fields apply the use of MIG (Metal Inert Gas) welding for various jobs in steel construction, especially mild carbon steel. MIG welding has good welding results and fast welding time efficiency. The purpose of this study is to analyze the tensile strength of welded joints on low carbon steel using MIG welding. The experimental method used in this study is to perform MIG welding on low-carbon steel plate profiles. The welded carbon steel is used as a test specimen and is formed according to the ASTM E8-M standard. Tensile testing is performed using a Shimadzu UH-300 kN type tensile testing machine. From this study, the tensile strength value of the test specimen welded by MIG (Metal Inert Gas) welding is higher than the tensile strength of the parent metal (low carbon steel), so this shows the strength of the weld joint. The average value of tensile strength on the test specimen is (σ) 507.40 N/mm2 and average strain (ɛ) 3.63%. The MIG welding process, between the base metal and filler metal with different chemical compositions, can cause mixing and a dilution effect of two compositions.